EAACI Guidelines on the effective transition of adolescents and young adults with allergy and asthma. Issue 11 (21st July 2020) - Roberts, Graham; Vazquez‐Ortiz, Marta; Knibb, Rebecca; Khaleva, Ekaterina; Alviani, Cherry; Angier, Elizabeth; Blumchen, Katharina; Comberiati, Pasquale; Duca, Bettina; DunnGalvin, Audrey; Garriga‐Baraut, Teresa; Gore, Claudia; et al.
Abstract: Adolescent and young adult (AYA) patients need additional support, while they experience the challenges associated with their age. They need specific training to learn the knowledge and skills required to confidently self‐manage their allergies and/or asthma. Transitional care is a complex process, which should address the psychological, medical, educational and vocational needs of AYA in the developmentally appropriate way. The European Academy of Allergy and Clinical Immunology has developed a clinical practice guideline to provide evidence‐based recommendations for healthcare professionals to support the transitional care of AYA with allergy and/or asthma. This guideline was developed by a multidisciplinary working panel of experts and patient representatives based on two recent systematic reviews. It sets out a series of general recommendations on operating a clinical service for AYA, which include the following: (a) starting transition early (11‐13 years), (b) using a structured, multidisciplinary approach, (c) ensuring AYA fully understand their condition and have resources they can access, (d) active monitoring of adherence and (e) discussing any implications for further education and work. Specific allergy and asthma transition recommendations include (a) simplifying medication regimes and using reminders; (b) focusing on areas where AYA are not confident and involving peers in training AYA patients; (c) identifying and managing psychological and socio‐economic issues impacting disease control and quality of life; (d) enrolling the family in assisting AYA to undertake self‐management; and (e) encouraging AYA to let their friends know about their allergies and asthma. These recommendations may need to be adapted to fit into national healthcare systems.